The morphometrical characteristic of the elements of the heart conduction system in the acute myocardial ischemia. - Bodnar L.V. (Морфологія, 2007)
. Information of morphometric research of structural elements of the heart conduction system in 20 dying from an acute coronary failure and 40 dying from an acute myocardial infarction with determination of diameter of heart conduction myocytes and area of their karyon is resulted in the article by establishment of by volume maintenance of tissues compo-nents of sinoatrial and atrio-ventricular nodes with the use of computer analyzer of image “Olympus DP-Soft”. In the ex-plored groups both atrophy and hypertrophies changes of heart conduction myocardium, increasing of by volume mainte-nance of stromal component as the display of compensational processes was founded.